The Vanderbeekers make a wish - Glaser, Karina Yan (Glaser, Karina Yan. Vanderbeekers, 2021)
One hilarious Harlem family is on a mission to find the perfect way to celebrate their Papa's fortieth birthday while discovering more about their mysterious grandparents in this heartfelt romp and latest installment to the New York Times best-selling series, perfect for fans of the Penderwicks. It's summer on 141st Street, and the Vanderbeekers are looking forward to Papa's surprise fortieth birthday party. But then Papa must leave town to help his best friend and the Vanderbeeker children are surprised to find their maternal grandparents on their doorstep. Grandma is very critical of everything they do. Meanwhile, they find themselves learning more about their papa's father than ever before, and wishing they could have known him a bit better. Can they learn more about the grandfather they lost and come to appreciate the grandparents they still have while making sure their papa has the best birthday ever?